Determination of ABO blood group based on secretors or non-secretors analysis in body fluids - Setiawan, Fery; Yudianto, Ahmad; Nurdianto, Arif Rahman; Sunariani, Jenny; Mooduto, Latief (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Criminal acts often leave traces analyzed by law enforcement, especially by the Indonesian National Police (POLRI). Sometimes, various items were found and analyzed to link the victim and the perpetrator. Blood, the most abundant body fluid, found in crime scenes, consists of cellular and liquid elements. The forensic focuses on red blood, which can be wet or dried at the crime scene. Sometimes, there was no blood or bloodstains found, but objects related to other body fluids, such as: condoms, toothbrushes, the mouth of glass cups, straws, etc, could be found. Blood group analysis could still be carried out based on secretor gene (Se) considering that 80% of the population was of the secretor group. There are two chromosomes related to blood regulation, namely: chromosomes no. 9 and 19. The former relates to the ABO blood group and the latter relates to the secretory phenotype. The basic principle of secretors was antigens found on the surface of red blood cells and all body fluids, except cerebrospinal fluid. The pattern of inheritance on chromosomes 9 and 19 is based on the probability law by Mendell. It stated that all of genotypes (homozygous dominant-recessive or heterozygous) would be passed on to their offspring.